2018
DOI: 10.1016/j.applthermaleng.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying EGR with split injection strategy on combustion performance and knock resistance in a spark assisted compression ignition (SACI) engine

Abstract: Spark assisted compression ignition (SACI) is a proven method for extending the load range and controlling the combustion phase of homogeneous charge compression ignition (HCCI) while maintaining high thermal efficiency. However, the occurrence of abnormal combustion, such as knock, limits the improvement of efficiency in SACI combustion. In this study, the effects of a coupling strategy, which combines internal/external exhaust gas recirculation (i & e-EGR) and split injection, on knock suppression in SACI mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 40 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In other words, thermodynamic conditions and chemical composition of the combustible mixture at intake valve closing (IVC) define the timing and duration of subsequent combustion process. Some additional controllability after IVC can, however, be introduced by means of direct injection (DI) of fuel, providing mixture stratification [11,12], or by socalled spark assist technology [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, thermodynamic conditions and chemical composition of the combustible mixture at intake valve closing (IVC) define the timing and duration of subsequent combustion process. Some additional controllability after IVC can, however, be introduced by means of direct injection (DI) of fuel, providing mixture stratification [11,12], or by socalled spark assist technology [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…When considering the mean value of MFBtrans, it decreases by about 3% at 473 K Tintake with advancing ST. However, advancing ST has increasing trends in the mean values of MFBtrans at Tintake of 498 and 523 K. 41 These may be explained with that decreasing compression heat addition to initial thermal state at the onset of combustion due to advancing ST requires a higher percentage of MFB consumed by the flame propagation. It can also be stated that the advanced ST from −30 °CA to −40 °CA has a little effect on MFBtrans 46 at 523 K Tintake that is already sufficient to initiate the combustion process at early stage relative to 473 and 498 K.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, the transition point was identified using the first maximum point of the second derivate of HRR ( d 2 HRR / d θ 2 ) . 41,42 A typical HRR curve of SICAI combustion has an inflection point ( T ) which brings about the maximum point on HRR″ curve, as shown in Figure 3. Thus, MFB of flame propagation (SI combustion) is also determined by the CAtrans point.…”
Section: Experimental Studymentioning
confidence: 99%
“…However, these technologies operate in a limited range of engine conditions closing to the combustion stability boundaries [2][3][4]. In this case, combustion failure such as misfire [5,6] and knock [7,8] happen under slightly mismatching of in-cylinder conditions. To achieve promising performance, advanced combustion control strategies are demanded.…”
Section: Introductionmentioning
confidence: 99%